The impact of PROGRESA on work, leisure, and time allocation: final report - Parker, Susan W.; Skoufias, Emmanuel (International Food Policy Research Institute, 2000)
This report analyzes the impact of PROGRESA on work and time allocation of its beneficiaries. In PROGRESA, the majority of benefits are linked to children’s school attendance. The fact that benefits are conditioned to children’s school attendance implies that the price of schooling is reduced. This would tend to imply, for children, an increase in school and a reduction in the participation of time spent in other activities, assuming that school and work are substitutes. With respect to adults, one might expect that a program with monetary transfers would reduce the labor supply of adults by reducing the economic need to work (through the income effect). Nevertheless, if children are now unable to perform certain work activities, other household members may substitute for their work. A final issue is the point that compliance with the obligations of PROGRESA may be time consuming especially for women. This may have the additional effect of either reducing the time available of women to dedicate to other work activities or of reducing their leisure time. The report has two main sections based on progressively broader definition of what constitutes work. In the first, we define work activities we estimate the impact of PROGRESA on work activities of men, women and children using before and after program implementation data (including the November 1997 census (ENCASEH), and the November 1998, June 1999 and November 1999 rounds of the evaluation survey (ENCEL). In the second, we use a special time use module carried out as part of the June 1999 evaluation survey (ENCEL) to look at the impact of PROGRESA on leisure time, as well as time allocated to different work activities, and school in the case of children. The time use module allows us to use a broader definition of work which include domestic and farm activities. The module also allows us some insights as to whether the time obligations of complying with the requirements of PROGRESA are important for female beneficiaries.